An experimental investigation on the quasi‐brittle fracture of marble rocks. Issue 8 (4th March 2016) - Spagnoli, Andrea; Carpinteri, Andrea; Ferretti, Daniele; Vantadori, Sabrina
Abstract: Natural stones like marbles are often employed as façade panels to externally cover buildings. These natural materials tend to exhibit a quasi‐brittle nonlinear fracture behaviour that, conversely to concrete counterpart, has much less been studied. In the present paper, an experimental campaign on the Mode I fracture of the so‐called red Verona marble is carried out, and the results are discussed together with some previously published results on the white Carrara marble. The analysis of the two marbles allows us to discuss size effect and to point out the need for additional parameters in order to describe their fracture behaviour. The study focuses on a two‐parameter model that accounts for a characteristic material length. An interpretation of the experimental results by means of both a work‐of‐fracture method and a size effect law is also presented. Full‐field displacement maps of the fracture process zone (experimentally obtained through a digital image correlation technique) are discussed in order to establish a quantitative correlation with material microstructure features, obtained from thin section technique, and some characteristic material length, based on the previously mentioned models.